Opportunity to Get Rich Before Getting Old : Analyzing the Demographic Capabilities of Bihar - Yadav, Ekta; Mujoo, Rachna (Arthshastra Indian Journal of Economics & Research, 2025)
Purpose : Bihar is one of India’s poorest but youngest state economies. As demographic developments took place, the age composition of the state changed. The study aimed to examine the impact of demographic dynamics on Bihar’s growth prospects. Methodology : The study adopted an analytical and explanatory research design rooted in a deductive approach. Engle–Granger causality, bivariate ARDL–ECM, and vector error correction model (VECM) were employed for the analysis, using data processed in EViews 12. Findings : The ARDL and VECM analyses revealed that the working-age population had a positive impact on economic growth, while the growing dependency ratio, particularly among children, had a significant negative effect. The old-age population’s growth also negatively affected the economy, though weakly. Practical Implications : Bihar faced the challenge of an aging population, which required attention to healthcare, social protection, and active aging initiatives. To fully capitalize on its demographic advantage, the state needed to focus on strategic reforms in governance, rural development, and entrepreneurship, while preparing for the socio-economic complexities of an aging society. Originality : The study’s originality lay in its focus on Bihar, a region often overlooked in macroeconomic and demographic discussions. Employing advanced econometric techniques (ARDL and VECM), it provided an in-depth understanding of how demographic dynamics impacted economic development, highlighting the risk of unexploited demographic advantages becoming future liabilities.